2001
DOI: 10.1200/jco.2001.19.18.3852
|View full text |Cite
|
Sign up to set email alerts
|

United States Multicenter Study of Arsenic Trioxide in Relapsed Acute Promyelocytic Leukemia

Abstract: This study establishes ATO as a highly effective therapy for patients with relapsed APL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
537
1
14

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 759 publications
(561 citation statements)
references
References 20 publications
9
537
1
14
Order By: Relevance
“…With subsequent ATO treatment or HSCT, the 18-month OS and relapse-free survival were 66% and 56%, respectively. 81 Alimoghaddam et al 87 have also conducted similar research in which 31 patients who relapsed from ATRA plus chemotherapy were reinduced to remission and consolidated by a single agent of ATO. After a median time of 32 months of follow-up, it was found that 10 (41.6%) patients relapsed in the 24 CR2 patients.…”
Section: Management Of Relapsementioning
confidence: 99%
“…With subsequent ATO treatment or HSCT, the 18-month OS and relapse-free survival were 66% and 56%, respectively. 81 Alimoghaddam et al 87 have also conducted similar research in which 31 patients who relapsed from ATRA plus chemotherapy were reinduced to remission and consolidated by a single agent of ATO. After a median time of 32 months of follow-up, it was found that 10 (41.6%) patients relapsed in the 24 CR2 patients.…”
Section: Management Of Relapsementioning
confidence: 99%
“…They have also been utilized clinically to treat various human diseases including psoriasis, syphilis, and rheumatosis. Recent clinical use of trivalent arsenic as an anticancer drug, especially in the treatment of acute promyelocytic leukemia [1][2][3], has stimulated intense interest in elucidating the underlying mechanisms of arsenicinduced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…We were interested in magnifying the efficacy of As 2 O 3 using substances that might be transferable to clinical application because the clinical applications of As 2 O 3 gain in importance not only for therapy of relapsed and refractory APL [29,30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], but also for treatment of multiple myeloma [48][49][50], myelodysplastic syndromes [51][52][53], and renal cancer [54]. Recently, two reports described apoptosis induction, caspase activation and ROS production by very high concentrations (up to 40 µM) of potassium antimonyl tartrate in lymphoid tumor cell lines [55] and growth inhibition and induction of apoptosis and reactive oxygen species [56].…”
Section: Discussionmentioning
confidence: 99%